Birth preparedness and complication readiness knowledge, practices and its associated factors among recently delivered women: A cross-sectional study in Bharatpur, Chitwan, Nepal - Asmita Ghimire; Bipan Bahadur Tiwari; Eak Narayan Poudel; Mamta Chhetri; Devraj Regmi; Laxman Poudel (PLoS ONE, 2026)
Background Birth preparedness and complication readiness (BPCR) is a comprehensive strategy, aimed at ensuring that expectant mothers and their families are for normal delivery and preparing for potential complications that may arise during pregnancy, labor, delivery, and the postpartum period without any delays. BPCR interventions are widely promoted by government and international agencies to reduce maternal and neonatal health risk in developing countries like Nepal. Studying BPCR also helps identify gaps in knowledge, access, and practices, guiding interventions to strengthen health system and community awareness, especially in low-resource settings. Objective This study was conducted to assess birth preparedness and complication readiness knowledge, practices and its associated factors among recently delivered women in Bharatpur city, Chitwan, Nepal. Methods A community based cross-sectional study was conducted in 2022, on a sample of 220 recently delivered women. Data were collected using pre-tested structured interview questionnaire. The collected data were analyzed by IBM SPSS 20 version software. Variables with p-value ≤0.05 on the bivariate analysis were included in multivariate analysis. Adjusted odds ratios (AOR) with the respective 95% Confidence Interval (CI) and a p-value <0.05 was used to set statistically significant variables in the multivariable analysis. Results Among 220 recently delivered women, majority (91.4%) of the women identified the place of delivery and saved money for childbirth (97.7%). Similarly, most of them arranged transportation (87.3%), identified a companion (85.9%), and arranged necessary materials (90%) for childbirth. Considerable (52.3%) women identified skilled birth attendants. Preparedness for blood donors (36.4%) found to be low as compared to other components. Overall, 46.8% of recently delivered women were well prepared. Family type, knowledge on components of BPCR, obstetric signs and symptoms and ANC visits were found to be statistically significant (p-value<0.05) with birth preparedness practice. Associated characteristics were further subjected to multivariate logistic regression where knowledge on components of BPCR (AOR = 5.34,95%CI: (2.728–10.478) was found significantly associated with BPCR practice. Conclusion The overall 46.8% of women who prepared for birth and its complication readiness was found to be higher as compared to other reports. Encouraging women to utilize antenatal care, and such as sensitization of pregnant women, during ANC visit by the health workers, regarding components of BPCR, danger sign and symptoms during pregnancy, may enhance BPCR.